Peningkatan Minat Belajar Siswa Melalui Model Pembelajaran Project Based Learning di Kelas IV Sekolah Dasar Negeri 76/IX Mendalo Darat - Tanita Anggun Saputri; Tika Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Fourth-grade students of SD Negeri 76/IX Mendalo still show low learning motivation in Natural Sciences and Social Sciences (IPAS) subjects. This is evident from their low attention, lack of enthusiasm, and tendency to chat during learning, which is caused by teachers not implementing appropriate learning methods and media. This study was conducted to increase student interest through PJBL with the use of audiovisual media, by means of a Classroom Action Research (CAR) methodology, separated into two cycles, with each cycle consisting of two meetings. Observation, worksheets, and questionnaires were the methods that were utilized to obtain data from the 21 students who participated in the research. An increase of 19.9% was observed in the average level of learning, which went from 62.7% in Cycle I to 82.6% in Cycle II respectively. All indicators of motivation, engagement, interest, enjoyment, and